A case report: ruptured primary ovarian abscess in pregnancy - Pratapwar, Dinesh D.; Bhure, Namdev M.; Zunjare, Sarika P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Primary ovarian abscess during pregnancy is a very rare entity. The clinical presentation is very vague and hence can be a diagnostic dilemma. Diagnostic laparoscopy gives a definitive diagnosis and an opportunity to treat the entity in same settings. Herein we discussed a case of a ruptured primary ovarian abscess in pregnancy which was successfully managed by laparoscopy. Ovarian abscess is different from tubo-ovarian abscess. A delay in diagnosis may be associated with risk of maternal death and can be detrimental to the fetus also. Surgical drainage of ovarian abscess and conservative and minimally invasive surgical procedure under antibiotics are recommended during pregnancy.